Empowerment of Beef Cattle Livestock by Bone District South Sulawesi Province - Ani Martini; Muhammad Anwansa Wandi (Institut Pemerintahan Dalam Negeri (IPDN), 2019)
This study aims to describe how Empowerment of Beef Cattle Breeders by the LivestockService Office of Bone Regency, South Sulawesi Province. The study was conductedthrough direct observation in the field to extract data through interviews and supportedby relevant literature reference sources to analyze data findings. This research usesdescriptive qualitative method with inductive approach. The author uses the theory ofAdisasmita (2006: 35), community empowerment is an effort to utilize and managerural community resources more effectively and efficiently, with indicators of inputaspects, process aspects, output aspects. The results of this study indicate that basedon the indicators of community empowerment proposed by Adisasmita, theEmpowerment of Beef Cattle Breeders by the Animal Husbandry Department of BoneRegency is not optimal because there are several obstacles in the communityempowerment.